Fit by adaptation or fit by founding? A comparative study of existing and new entrepreneurial cohorts in China - Zhang, Chenjian; Tan, Justin; Tan, David (Strategic Management Journal, 2016)
Extant research provides ambiguous views on the network adaptability of existing ventures and new ventures during environmental change. Applying an institutional perspective, this research aims to provide a clearer picture by comparing the adaptation and network configurations of existing vs. new entrepreneurial cohorts during China's institutional change after 1992. The qualitative and quantitative analyses show that the existing cohort of entrepreneurs displays network inertia, in that they largely maintain strong tie‐based political and market networks; the new cohort instead demonstrates better adaptation by establishing fewer political networks but more weak and diverse market networks. This comparative research unpacks the institutional mechanisms underlying such differences, and serves as a ground for future investigations dealing with the strategic actions of different entrepreneurial cohorts that are largely neglected in previous studies . Copyright © 2014 John Wiley & Sons, Ltd.